Peranan Parameter Quench dan Temper Pada Ketangguhan Carbon-Manganese Steel - Akhlis Rahman Sari Nurhidayat; Nur Akhlis Sarihidaya Laksana; Yurianto Yurianto (P3M Politeknik Negeri Cilacap, 2023)
The use of material that is specified as armor steel has a high resistant value. The quenching and tempering process is done to improve the toughness of the material. The process uses a temperature of 900oC on the quenching process with water medium and tempering temperatures of 125oC and 175oC holding time for 30 minutes. The tests include the impact test to determine the increase in the material and fractography to determine the ductility of the material. There is a decrease in the value of the impact that occurs after the quenching process. The impact value is increasing due to the tampering impact of 32 J during the quenching process to 50 J. The fractography shows brittle fractures with ridges as a feature of brittle fractures. Rapid cooling rate processes in the quenching process cause cracks in the quenching specimens.